Chronographical Spatiotemporal Scheduling Optimization for Building Projects - Francis, Adel (Frontiers in Built Environment, 2019)
The arrival of building information modeling and four-dimensional (4D) simulation is forcing the construction industry to adapt its contractual, operational and technical modes. Currently, the 4D simulation model is either a bar chart or a linear diagram. Both methods are unsuitable for modeling building projects, as showing the work sequence, circulation and supply flow between sites is difficult. Spatiotemporal planning is more suitable as a scheduling model, as it considers activities, resources, and spaces simultaneously. However, most of the optimization process based on space planning uses deterministic or stochastic optimization techniques, and these techniques are not viable enough to apply to building construction schedules. The number of parameters is too important for one to consider using algorithmic optimization only. Therefore, this paper proposes a hybrid solution based on spatiotemporal techniques that combine graphical, procedural and algorithmic aspects. The integration of spaces and operations ensures the continuity of use of spaces and teams, as well as linear production. An approach that prioritizes the critical space on the critical path of activities.